Aptamer-functionalized gold nanoparticles for fast and selective electrochemical sensing of lead in tobacco - Zhang, Liang; Wu, Jinming; Xiao, Mingli; Zhang, Shuo; Ren, Shengchao; Luo, Dongsheng; Xi, Feihu; Liu, Huan; Li, Yaoguang; Li, Quansheng; Jing, Yanqiu (International journal of electrochemical science, 2024)
This study presents a novel electrochemical aptasensor for the ultrasensitive detection of lead(II) ions in tobacco products. The sensor utilizes a G-quadruplex forming DNA aptamer (5′-GGGTGGGTGGGTGGGT-3′) immobilized on gold nanoparticles (AuNPs) with an average diameter of 73.2 nm. The aptamer-Pb2+ interaction, characterized by circular dichroism and isothermal titration calorimetry, revealed a dissociation constant of 0.28 ± 0.03 μM. Optimized sensor fabrication conditions included 1 μM aptamer concentration and 16-h incubation time. The aptasensor exhibited two linear ranges: 0.2072–103.6 μg/L and 103.6–1072 μg/L, with a detection limit of 37 ng/L. The sensor maintained selectivity in the presence of interfering ions at 100-fold higher concentrations. The sensor demonstrated excellent stability, retaining 92.1 % of its initial response after 30 days, and high reproducibility with an inter-batch RSD of 5.3 %. This aptasensor offers a promising platform for rapid and sensitive Pb2+ detection in complex matrices.